Note: Derivative divide, a method for the analysis of broadband ferromagnetic resonance in the frequency domain - Maier-Flaig, Hannes; Goennenwein, Sebastian T. B.; Ohshima, Ryo; Shiraishi, Masashi; Gross, Rudolf; Huebl, Hans; Weiler, Mathias (Review of Scientific Instruments, 2018)
Broadband ferromagnetic resonance (bbFMR) spectroscopy is an established experimental tool to quantify magnetic properties. Due to frequency-dependent transmission of the microwave setup, bbFMR measurements in the frequency domain require a suitable background removal method. Here, we present a measurement and data analysis protocol that allows us to perform quantitative frequency-swept bbFMR measurements without the need for a calibration of the microwave setup. We furthermore compare the results of the proposed frequency space analysis and a conventional analysis in field-space of bbFMR data obtained from a permalloy thin film. The very good agreement of the extracted parameters using the two methods shows the reliability of our method.
CRIS-Team Scopus Importer:2023-03-27